Morphological and molecular assessment of large sea anemones (Actiniaria: Actiniidae) in Newfoundland (eastern Canada) - Sanamyan, N. P.; Sanamyan, K. E.; Mercier, A.; Hamel, J.-F.; Bocharova, E. S. (Polar Biology, 2020)
Literature records of large actiniid sea anemones along the Atlantic coast of Canada currently include three Urticina species: U. felina, U. fecunda and U. crassicornis. The findings of the present morphological and molecular study conducted in eastern Newfoundland suggest that U. felina is often misidentified, and that this region may only harbor two similar-looking species: U. crassicornis and Cribrinopsis similis. The latter were identified using genetic analysis and comparison of key characters with the same species collected from other regions of the North Atlantic (Barents Sea), whereas no specimen corresponding to U. felina was found. Mitochondrial gene sequences of U. crassicornis, U. felina and C. similis were identical except for a different haplotype found in several specimens of U. crassicornis (with one nucleotide substitution), in contrast to five nucleotide insertions in 16S rRNA fragments of U. fecunda. Phylogenetic analysis based on three mitochondrial and two nuclear gene fragments revealed that the most closely related species among the above-mentioned were U. crassicornis and U. felina, nevertheless U. fecunda groups in the same clade as the Urticina species.